Welfare Impacts of Policy Reforms: A Case of Electricity Subsidies in Pakistan - Ilyas, Rubina; Ullah Khan, Hidayat; Rauf, Abdur (International Journal of Energy Economics and Policy, 2022)
Pakistan has been paying more than 2% of its GDP as electricity subsidies. However, these subsidies continue to be poorly targeted benefiting the rich household’s disproportionately. This study aims to assess the efficiency of the power policy reform 2013 by conducting a benefit incidence analysis for the year 2012 and 2015. It also analyzes the impact of a uniform and non-uniform increase in the tariff structure on the subsidy distribution and household welfare. The study reveals that though the power policy reform (2013) have improved the tariff structure for the poor, there is still significant leakage to the richest HHs. Analyzing the impact of a uniform and non-uniform increase in tariffs across the consumption slabs shows that despite targeting the higher slabs, the benefit incidence does improve for poor but it remains limited. While it does decrease for the rich however they still benefit from the subsidies. In such a situation the benefit incidence can be improved by charging higher tariff rates for consumers having higher consumption of electricity. For example, the tariff structure can be revised for consumers using more than 300kWh by charging them a rate at least equal to the cost of supply for slabs below 300kWh.